A Model for Evaluating Logistics Services Providers: Case Study in a Chilean Chemical Company - Sepulveda-Salas, J (2013)
In this paper an actual application of a supplier evaluation and classification model is presented. The novelty of the work is the use of Flowsort™, a new multicriteria decision making method for sorting purposes based on the classical Promethee approach. Instead of a common supplier ranking, the model classifies providers in order to decide the continuation of their services as logistics providers, continue with correcting measures, or to quit providing services due to low performance. An example of the application is developed. © IFAC.